The Creation of the Convenient Investment Strategy in Forex - Majerčáková, Daniela; Greguš, Michal (European Journal of Economics and Business Studies, 2019)
Forex that belongs into the biggest and the most widespread financial markets in the world has the daily turnover that is assessed to more than 5 trillion USD. This fact is at the same time a temptation for investors and attracts them to trade in this market. Only the small percentage from this daily turnover is made of the business of governments and companies, that purchade in foreign countries or need to exchange foreign currency for the domestic one. The majority consists of the speculative business. Speculative business is based on the expectations of a speculator on the future rise or fll of exchange rate, that he plans to earn money on. In this case, we are talking about the market with unpredictable environment. It is controlled by the crowd of people who create the most extensive financial market of the world by their mutual purchasing and selling foreign currencies. The aim of this paper is to create the convenient investment strategy on the basis of the analysis of foreign exchange market. We have used the description for the fulfillment of this aim and consequently we have focused on business strategies as the fundamental and technical analysis and its use in the real trading. We have described the development of trading in the chosen market and period by means of fictitious account on the platform Metatrader4. Consequently, we have analysed the influence of the particular factors on the results of investing in Forex
Keywords: Forex, currency pair, currency graphs, investment strategy, analysis